Seasonal variation in Aspergillus abundance in captive penguin burrow sands and its implication for aspergillosis risk in Japan - Takanobu, Shiori; Araki, Yuri; Nitta, Rie; Shindo, Hideaki; Matsumoto, Naoya; Itoh, Megumi; Yamada, Kazutaka; Toyotome, Takahito (Frontiers in Veterinary Science, 2026)
BackgroundAspergillosis is a major fungal disease in penguins. However, seasonal variation of Aspergillus spp. in burrow sands and its association with meteorological factors remain poorly characterized, particularly under Japan’s climatic conditions.ObjectivesThis study aimed to examine seasonal changes in Aspergillus spp. abundance in Humboldt penguin burrows and test whether temperature and other environmental factors correlated with fungal positivity.MethodsFrom June 2023 to October 2024, 158 sand samples were collected from burrows and surrounding areas at an outdoor Humboldt penguin (Spheniscus humboldti) facility in Shimonoseki, Japan. Fungal colonies were cultured and identified morphologically and by sequencing.ResultsAspergillus spp. positivity peaked from July to October in both years. Average temperature showed strong positive correlation with fungal positivity (r = 0.781, p < 0.01), while other meteorological factors exhibited weaker associations. Multiple Aspergillus spp. were identified, including known pathogenic Aspergillus sections Fumigati, Nigri, Flavi, and Terrei.ConclusionTemperature demonstrated the strongest correlation with Aspergillus spp. positivity, suggesting seasonal monitoring is critical for managing aspergillosis risk in captive penguins. These findings provide a basis for future multi-site studies to improve fungal disease prevention strategies.